60.5k views
0 votes
Explain how you will evaluate 4[ 3(62+1)] - 63

User Anuga
by
5.4k points

2 Answers

4 votes

Answer:

720

Explanation:

First you do the things inside the parenthesis which is 62 + 1 = 63

Which gives you this -----> 4[ 3 x 63]-36

Then do the brackets (brackets are these btw "[ ]" )

After doing the brackets you should bet this 4 x 189 - 36

Then you do the multiplication -----> 756 - 36

756 - 36 = 720

User Zahmati
by
5.3k points
2 votes

Answer:

693

Explanation:

You can simply apply BODMAS(Bracket of Division Multiplication Addition Subtraction)

Here, the brackets come first

62+1=63

63*3=189

189*4=756

756-63=693

User IClaude
by
5.5k points